PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL, DAN IOS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BEI. - Alamsyah, Agus Rahman (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
The long-term goal of this research is to test the effectiveness of financial management theory and research. The research method is explanatory (explanatory research) that research is done to confirm and test whether there is relationship or influence between variables, that is specifically will be tested hypothesis in structural equation. Causal research is a study designed to identify the cause and effect of each relationship between variables on a clearly defined research problem. This research uses data pooling that is merging between time series and cross section data. In this study, the analysis used to test the five hypotheses through path analysis technique and SPSS program version 23. Path coefficient is standardized regression coefficient. The path coefficient is calculated by making two structural equations ie the regression equation showing the hypothesized relationship. The result of this research is the ownership structure having negative and significant effect to the dividend policy; Capital structure has no effect on dividend policy; Capital structure has a positive and significant impact on firm value; The ownership structure affects firm value through dividend policy, or dividends mediating the influence of ownership structure on firm value. Capital structure does not affect the value of the company through dividend policy, but it directly affects the value of the company.